Development Of an Automated Workstation for A Specialist in Dermatovenerology - Mominov Murodjon Mansuridinovich (Zien Journals, 2024)
The article discusses the issues of creating an automated workstation (AWS) for a medical specialist. Using the example of the development of an automated workstation for a dermatovenerologist, its functionality and methods of interaction with other structural elements in the system of providing dermatovenereological care to the population are shown. Based on the developed automated workplace, an algorithm for the work of a dermatovenerologist is proposed
Keywords: automated workstation for a dermatovenerologist; medical decision support systems; medicine; dermatovenerology